2017
DOI: 10.1042/bcj20170132
|View full text |Cite
|
Sign up to set email alerts
|

Hiding in plain sight: immune evasion by the staphylococcal protein SdrE

Abstract: The human immune system is responsible for identification and destruction of invader cells, such as the bacterial pathogen In response, brings to the fight a large number of virulence factors, including several that allow it to evade the host immune response. The staphylococcal surface protein SdrE was recently reported to bind to complement Factor H, an important regulator of complement activation. Factor H attaches to the surface of host cells to inhibit complement activation and amplification, preventing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In the process of adhesion, cell surface proteins (adhesins) of the Microbial Surface Component Recognizing Adhesive Matrix Molecules (MSCRAMM) play an important role in the pathogenesis of osteoarticular infections (OM and PJIs). Among these, an important role is played by: the fibronectin‐binding proteins A and B (FnbA/B); the fibrinogen‐binding protein clumping factors A and B (ClfA/B); the bone sialoprotein binding protein (Bbp); the collagen adhesin (CNA) (Otsuka et al, 2006; Pérez‐Montarelo et al, 2018); and SdrE, a serine–aspartate (SD) protein that anchors the cell wall interacting with complement factor H and facilitates colonization through adherence to the cell surface or extracellular matrix (ECM) components (Herr & Thorman, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the process of adhesion, cell surface proteins (adhesins) of the Microbial Surface Component Recognizing Adhesive Matrix Molecules (MSCRAMM) play an important role in the pathogenesis of osteoarticular infections (OM and PJIs). Among these, an important role is played by: the fibronectin‐binding proteins A and B (FnbA/B); the fibrinogen‐binding protein clumping factors A and B (ClfA/B); the bone sialoprotein binding protein (Bbp); the collagen adhesin (CNA) (Otsuka et al, 2006; Pérez‐Montarelo et al, 2018); and SdrE, a serine–aspartate (SD) protein that anchors the cell wall interacting with complement factor H and facilitates colonization through adherence to the cell surface or extracellular matrix (ECM) components (Herr & Thorman, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the process of adhesion, cell surface proteins (adhesins) of the Microbial Surface Component Recognizing Adhesive Matrix Molecules (MSCRAMM), play an important role in the pathogenesis of osteoarticular (OM and PJ) infections. Among these, fibronectin binding proteins A and B (FnbA/B), fibrinogen-binding protein clumping factors A and B (ClfA/B), the bone sialoprotein binding protein (Bbp), the collagen-adhesin (CNA) (Perez-Montarelo et al, 2018;Otsukaet al , 2006) and SdrE, a serine-aspartate (SD) protein that anchors the cell-wall interacting with complement Factor H and facilitates colonization through adherence to the cell surface or extracellular matrix (ECM) components (Herr and Thorman, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…SdrD was noteworthy as an adhesin that was highly resistant toward digestion (Tables , , and ) and yet has no known blood borne binding partners. Its only known partner is the keratinocyte surface protein desmoglein 1, , promoting S. aureus nasal colonization (Table ). Recent work showed that the expression of SdrD improved survival of Lactococcus lactis in human blood, possibly by inducing killing of neutrophils, implying that SdrD does have one or several more binding partners in blood to be identified …”
Section: Discussionmentioning
confidence: 99%